Theorgano-mineral fertilization on the yield of faba bean in soil and hydroponics in protected agriculture - Vela Coyotl, Maria de los Angeles; López Tecpoyotl, Zenón Gerardo; Sandoval Castro, Engelberto; Tornero Campante, Mario Alberto; Cobos Peralta, Mario Antonio (Revista Mexicana de Ciencias Agrícolas, 2018)
The faba bean is a crop of great social and economic importance in the High Valleys of the Central Table of Mexico, having as a final destination the human and animal consumption. Despite its importance, grain yields are low, with inadequate fertilization being one of the reasons. The present investigation was carried out with the purpose of determining the effect of organo-mineral fertilization on the yield of faba bean, soil and substrate tezontle. The research was conducted from December 2013-April 2014, in the municipality of San Pedro Cholula, Puebla, under greenhouse conditions, using Cochinera Cultivation seed. Two factors were studied: foliar liquid biofertilization and Steiner nutrient solution concentration at 50% and 100%. The biofertilizers studied were from Taiwanese continuous flow digesters located in the municipalities of San Felipe Teotlalcingo and Huejotzingo, Puebla. The experimental design of the works was completely random and factorial treatment arrangement, with five repetitions. The results showed that, for the cultivation in soil, the treatments did not present differences in the yield of fresh fruit, but there were significant differences in yield of dry fruit where the application of liquid biofertilizer from San Felipe Teotlalcingo had the best results. While the application of a complete organo-mineral fertilization in tezontle substrate resulted in the best response in yield of fresh and dry fruit.